Slam! - Myers, Walter Dean, 1937- (New York : Scholastic Press, 1996)
Sixteen-year-old "Slam" Harris is counting on his noteworthy basketball talents to get him out of the inner city and give him a chance to succeed in life, but his coach sees things differently.
750
Accelerated Reader AR
Keywords: Basketball stories; Sports stories; Basketball -- Fiction; African Americans -- Fiction; High schools -- Fiction; Schools -- Fiction; Prejudices -- Fiction